Models for Seismic Vulnerability Analysis of Power Networks: Comparative Assessment. (4th February 2014) - Cavalieri, Francesco; Franchin, Paolo; Buriticá Cortés, Jessica A. M.; Tesfamariam, Solomon; Shinozuka, M.
Abstract Electric power networks are spatially distributed systems, subject to different magnitude and recurrence of earthquakes, that play a fundamental role in the well‐being and safety of communities. Therefore, identification of critical components is of paramount importance in retrofit prioritization. This article presents a comparison of five seismic performance assessment models (M1 to M5) of increasing complexity. The first two models (M1 and M2) approach the problem from a connectivity perspective, whereas the last three (M3 to M5) consider also power flow analysis. To illustrate the utility of the five models, the well‐known IEEE‐118 test case, assumed to be located in the central United States, is considered. Performances of the five models are compared using both system‐level and component‐level measures. Spearman rank correlation ρ is computed between results of each model. Highest ρ values, at both system‐ and component‐level, are obtained, as expected, between M1 and M2, and within models M3 to M5. The ρ values between component‐level measures are relatively high across all models, indicating that simpler ones (M1 and M2) are appropriate for vulnerability assessment and retrofit prioritization. The complex flow‐based models (M3 to M5) are suitable if actual performance of the systems is desired, as it is the case when the power network is considered within a larger set of interconnected infrastructural systems.